Reinterpretation of the Legend of Lake Toba into the Batak Opera Janji Putri Ikan - Octaviana Tobing; Russel Akbar Fauzi; Try Wahyu Purnomo (Budapest International Research and Critics University, 2021)
The creation of the Janji Putri Ikan Batak Opera is an effort to design the Art of Batak Opera which is based on the Batak folklore of the legend of Lake Toba. The design effort is the result of the re-interpretation of the legend of Lake Toba folklore through the transfer approach. The results of the transfer of the vehicle were initially manifested in a new drama play entitled Janji Putri Ikan. The drama play of the Janji Putri Ikan was designed by retaining the plot as found in the folklore of the legend of Lake Toba but changing it from a folklore format to a drama play format with a formulation or play style adapted for the purposes of designing the Batak Opera. The designer of the play is done by making changes to the structural aspects of folklore which are interpreted deconstructively in the meaning of the structure. The placement of the opposite meaning of the structure ultimately has an impact on significant changes in the characterization aspect, the dramatic aspect and also the story setting aspect as contained in the structure of the legend of Lake Toba folklore. Thus, the design of the Janji Putri Ikan Batak Opera is more than just an adaptation work but is a complete application of the concept of transfer from the regional literary genre (folklore) to the creation of the Batak Opera. This means that the final embodiment of this creation is the Batak Opera performance with the play Janji Putri Ikan. This work is supported by 15 players consisting of actors, dancers, and musicians, which will be performed at the local or national level. The product of this research is a work of theater art, as an appreciation material for students and the community. This work is made in Brechtian form in a realist concept.